2011
DOI: 10.1016/j.molbiopara.2010.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of Plasmodium falciparum dipeptidyl aminopeptidase 1

Abstract: Dipeptidyl aminopeptidase 1 (DPAP1) is an essential food vacuole enzyme with a putative role in hemoglobin catabolism by the erythrocytic malaria parasite. Here, the biochemical properties of DPAP1 have been investigated and compared to those of the human ortholog cathepsin C. To facilitate the characterization of DPAP1, we have developed a method for the production of purified recombinant DPAP1 with properties closely resembling those of the native enzyme. Like cathepsin C, DPAP1 is a chloride-activated enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 57 publications
6
60
1
Order By: Relevance
“…5 A and B). Further sequence analysis of the accumulated Hb-derived oligopeptides revealed that the majority were likely poor substrates for DPAP1, the other essential aminopeptidase with broad substrate specificity found in the DV (47). We thus hypothesized that PfA-M1 was necessary for proteolysis of these oligopeptides.…”
Section: Inhibition Of Pfa-m1 Kills Parasites Via Disruption Of Hb DImentioning
confidence: 97%
“…5 A and B). Further sequence analysis of the accumulated Hb-derived oligopeptides revealed that the majority were likely poor substrates for DPAP1, the other essential aminopeptidase with broad substrate specificity found in the DV (47). We thus hypothesized that PfA-M1 was necessary for proteolysis of these oligopeptides.…”
Section: Inhibition Of Pfa-m1 Kills Parasites Via Disruption Of Hb DImentioning
confidence: 97%
“…For example, a cytoplasmic aspartyl aminopeptidase (PfM18AAP), that is the only malaria aminopeptidase capable of cleaving aspartic and glutamic acids from the N-termini of peptides, is also present in single copy and is essential for parasite viability. 55 Also in consideration are the post-prolyl aminopeptidase (PfAPP) 32 and dipeptidyl peptidase (cathepsin C) 25,26 that are located in the DV and central to the later stages of hemoglobin degradation.…”
Section: Resultsmentioning
confidence: 99%
“…13,18,19 However, knockout experiments have shown that the DV plasmepsins and falcipains 2 and 2′ are individually not essential to parasite survival, and because of this redundancy between the function of these enzyme classes it has proved difficult to develop drugs that effectively block the digestive process within the DV. [21][22][23][24] Peptides produced in the DV may be further processed to dipeptides by a dipeptidyl aminopeptidase I, an orthologue of mammalian cathepsin C. 25,26 Small peptides and dipeptides may also be reduced to free aminoacids within the DV and/or transported to the parasite cytosol for processing by aminopeptidases. 20,[27][28][29][30][31][32][33] Aminopeptidases are essential in releasing aminoacids from haemoglobin-derived peptides and are thus central to the growth and development of malaria parasites in the erythrocyte.…”
Section: -16mentioning
confidence: 99%
“…Once FLN converts short globin polypeptides into oligopeptides consisting of 5-10 amino acids, dipeptidyl amino peptidase 1 (DPAP1), a lysosomal exopeptidase, sequentially cleaves oligopeptide substrates from their N terminus into dipeptides [87,130]. Attempts to disrupt the DPAP1 gene have been unsuccessful, which suggests that the enzyme makes an important contribution to hemoglobin catabolism during the intraerythrocytic cycle [131].…”
Section: Dipeptidyl Amino Peptidasementioning
confidence: 99%
“…Attempts to disrupt the DPAP1 gene have been unsuccessful, which suggests that the enzyme makes an important contribution to hemoglobin catabolism during the intraerythrocytic cycle [131]. While DPAP1 is one of the three related DPAP enzymes encoded in the parasite genome, current evidence suggests that only DPAP1 resides in the food vacuole [130]. DPAP1 is also potentially a good drug target because the closest human homologue is cathepsin C, a protease that is not essential in mammals [130,132,133].…”
Section: Dipeptidyl Amino Peptidasementioning
confidence: 99%